E-2: KNOWLEDGE MANAGEMENT DIMENSIONS AND JOB SATISFACTION: : MODERATING ROLE OF PERCEIVED ORGANIZATIONAL SUPPORT - malik, Safdar; Ajmal, Muhammad; Khan, Imran (International Journal of Islamic Business, Administration and Social Sciences (JIBAS), 2023)
The study aims to verify knowledge management's impact on job satisfaction with the moderating role of perceived organizational support. Job satisfaction of the employee increases in knowledge-based organizations. The present study examined the job satisfaction level of the public sector universities of the Punjab region employees with moderating effects of perceived organizational support. This model was developed from the literature review in which the research design was cross-sectional, and research data was collected through a questionnaire. A sample of 236 respondents was used to test the hypothesis. The main findings of the research reveal that job satisfaction exists with the moderating effect of perceived organizational support in two dimensions of knowledge management, i.e., knowledge sharing and knowledge creation. The result of this study indicates that knowledge management has a substantial impact on job satisfaction. Therefore, top management and higher authorities should encourage knowledge management practices in organizational culture to improve employee performance. Moreover, the results demonstrate that different employees benefit from various dimensions of knowledge management. Thus, it provides the guidelines for implementing knowledge management in different intra-organizational working environments.